2021
DOI: 10.1155/2021/6635630
|View full text |Cite
|
Sign up to set email alerts
|

Wear Characteristics of Dense Fine Particles Solid‐Liquid Two‐Phase Fluid Centrifugal Pump with Open Impellers

Abstract: The demand for a centrifugal pump with open impellers for conveying dense fine particles in solid-liquid two-phase flow has increased significantly in actual engineering. The wear of dense fine particles on the centrifugal pump is also exceedingly prominent, which affects the engineering efficiency and economic benefits. The two-phase flow in the open centrifugal pump is three-dimensional and unsteady; the movement of high-volume concentration particles in the centrifugal pump and its mutual influence on the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Noon and Kim (2016) applied Finnie erosion model to predict the erosion morphology of volute of lime slurry pump, and the results showed that the erosion rate of volute increased with the increase of impact velocity, mass concentration and particle size. Wang et al (2021) found that the wear of centrifugal pump impeller is greatly affected by relevant parameters such as pump flow, particle diameter and particle volume concentration. Lai et al (2021) predicted the wear characteristics of centrifugal pump wall based on E/CRC wear model and discussed the effects of particle size and concentration on EC 39,6 the wear characteristics of centrifugal pump impeller.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noon and Kim (2016) applied Finnie erosion model to predict the erosion morphology of volute of lime slurry pump, and the results showed that the erosion rate of volute increased with the increase of impact velocity, mass concentration and particle size. Wang et al (2021) found that the wear of centrifugal pump impeller is greatly affected by relevant parameters such as pump flow, particle diameter and particle volume concentration. Lai et al (2021) predicted the wear characteristics of centrifugal pump wall based on E/CRC wear model and discussed the effects of particle size and concentration on EC 39,6 the wear characteristics of centrifugal pump impeller.…”
Section: Introductionmentioning
confidence: 99%
“…Noon and Kim (2016) applied Finnie erosion model to predict the erosion morphology of volute of lime slurry pump, and the results showed that the erosion rate of volute increased with the increase of impact velocity, mass concentration and particle size. Wang et al. (2021) found that the wear of centrifugal pump impeller is greatly affected by relevant parameters such as pump flow, particle diameter and particle volume concentration.…”
Section: Introductionmentioning
confidence: 99%
“…In the Euler-Lagrange model, the solid particles are particularly tracked in the Lagrangian frame of reference, rather than being treated as an extra Eulerian phase. Complete information on the behavior and residence time of individual particles and better details regarding mass and heat transfer are available, but the method is expensive in terms of computational resource demand [18][19][20]. The Discrete Element Method (DEM) uses DEM and CFD methods to iteratively solve for the particle motion and the fluid flow field in order to achieve momentum balance between the liquid and solid phases.…”
Section: Introductionmentioning
confidence: 99%